Study of The Impact of Limestone Mining on Environmental Damage in Klapanunggal Village of Bogor Regency - Faizah Nur Fitriyah; Winarno Winarno (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2023)
Klapanunggal Village is one of the villages which is one of the places for limestone mining to be carried out. The existence of limestone mining which has been operating since 1970 has had a direct impact on the environment of the surrounding community. The purpose of this study is to determine the impact of limestone mining on environmental damage in Klapanunggal Village and to find out the efforts of the local government to reduce the negative impacts of illegal limestone mining in Klapanunggal Village , Bogor Regency. This research is a type of descriptive research. The research results obtained are damage and changes in landscapes, destruction of habitats and ecosystems in limestone hills/mountains, stagnant water or ponds resulting from mining residues, damaged and perforated road conditions, air pollution, and noise. As for the efforts of the government was a 1000 tree planting program but only in a few locations and also carried out road casting in several road areas.